2021
DOI: 10.1007/s12038-021-00209-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxins, the last-resort antibiotics: Mode of action, resistance emergence, and potential solutions

Abstract: Infections caused by multi-drug resistant (MDR) bacterial pathogens are a leading cause of mortality and morbidity across the world. Indiscriminate use of broad-spectrum antibiotics has seriously affected this situation. With the diminishing discovery of novel antibiotics, new treatment methods are urgently required to combat MDR pathogens. Polymyxins, the cationic lipopeptide antibiotics, discovered more than half a century ago, are considered to be the last-line of antibiotics available at the moment. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 156 publications
1
76
0
1
Order By: Relevance
“…Polymyxins (colistin and polymyxin B) are old antimicrobials, which have been used clinically since the late 1960s, acting against Gram-negative bacteria such as Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli ( Evans et al, 1999 ; Mohapatra et al, 2021 ). However, the clinical use of polymyxins has been restricted due to their side effects, such as neurotoxicity and nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Polymyxins (colistin and polymyxin B) are old antimicrobials, which have been used clinically since the late 1960s, acting against Gram-negative bacteria such as Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli ( Evans et al, 1999 ; Mohapatra et al, 2021 ). However, the clinical use of polymyxins has been restricted due to their side effects, such as neurotoxicity and nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The outer membrane is a distinctive feature of GNB that provides a barrier protecting GNB from exposure to unwanted chemical compounds, resulting in limited treatment options [ 12 , 41 ]. Among several proposed therapies for the further treatment of GNB infections [ 42 , 43 ], a combination of colistin with other antibiotics is considered a potential approach associated with overcoming the outer membrane permeability barrier, a broader antibacterial spectrum, synergistic effects and reduced risk for emerging resistance during therapy [ 20 , 44 , 45 ]. In addition, many studies have demonstrated that, in contrast to monotherapy, combination therapy may enhance antimicrobial effects and provide synergism [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these antibiotics are far from ideal therapeutic options to fully combat the emergence of MDR GNB infection [ 18 ]. Currently, polymyxins (such as polymyxin B (PMB) and colistin) are considered last-resort antibiotics for the treatment of MDR GNB infections particularly due to their specific targeting of the outer membrane [ 19 , 20 , 21 ]. Nonetheless, resistance to polymyxins is emerging via multiple mechanisms [ 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there is overwhelming evidence that polymyxins cause membrane disruption [23,32,33], additional mechanisms have been proposed to contribute to bacterial killing. These have been summarized in detail elsewhere [44] and so only a brief overview is provided here. Colistin, and other polymyxins, have been found to directly inhibit the enzymatic activity of the respiratory enzyme NDH-2 from E. coli, K. pneumoniae and A. baumannii [45].…”
Section: Polymyxinsmentioning
confidence: 99%